Optimalisasi Bioremediasi Minyak Bumi Menggunakan Pseudomonas Aeruginosa Hasil Rekayasa Genetik - Isnada, Isnada; Hala, Yusmina (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Petroleum contamination stands as one of the most serious environmental challenges, particularly affecting soil and aquatic ecosystems impacted by oil spills, pipeline leaks, and industrial activities. Pseudomonas aeruginosa is recognized as an effective biodegradative bacterium due to its natural ability to produce rhamnolipid biosurfactants and express oxidative enzymes such as alkane monooxygenase (AlkB). In the modern era of biotechnology, the genetic engineering of key genes, including alkB, rhlAB, and the transcriptional regulator LcaR, has opened up opportunities for a significant increase in hydrocarbon degradation. This study conducts a narrative systematic review of Scopus literature to identify the bioremediation mechanisms employed by P. aeruginosa and the contribution of genetic engineering toward enhancing hydrocarbon degradation efficiency. The analysis indicates that the bioremediation stages encompass chemotaxis, biosurfactant production, primary oxidation, $β$-oxidation, biofilm formation, and quorum sensing based molecular regulation. Genetic modifications are proven to enhance the rate of alkane oxidation, strengthen rhamnolipid production, and accelerate the activation of degradation pathways. These findings affirm that engineered P. aeruginosa-based strains hold significant potential for application in bioremediation scenarios in Indonesia, especially in regions with extreme conditions such as high salinity, fluctuating pH, or high oil concentrations. The results of this review provide a scientific foundation for the development of engineered microbial bioformulations as a sustainable solution for petroleum contamination management.